The Role of Cancer Stem Cells in Glioblastoma Treatment: New Strategies for Targeted Therapy - Yan, Kaize (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Glioblastoma (GBM) is a highly aggressive and recurrent brain tumor for which traditional treatments often yield limited success. According to recent research, cancer stem cells (CSCs) are essential for the development, spread, and resistance to treatment of GBM. This review systematically explores the critical roles of cancer stem cells (CSCs) in glioblastoma (GBM), especially through the regulation of Notch, Wnt, and Hh signaling pathways. The maintenance of CSC properties is primarily dependent on the Notch, Wnt, and Hedgehog (Hh) signaling pathways. This review explores the mechanisms of these pathways in GBM, discusses multi-targeted combination therapies, and highlights emerging strategies and drugs for targeted therapy. The results indicate that targeting Notch, Wnt, and Hh pathways can effectively suppress CSC proliferation and invasiveness in GBM, significantly delaying tumor recurrence. Future research should further explore the clinical potential of these pathway inhibitors and develop more specific targeted therapies to improve GBM treatment outcomes and patient prognosis.